A Journey of Cytolethal Distending Toxins through Cell Membranes - Boesze-Battaglia, Kathleen; Alexander, Desiree; Dlakić, Mensur; Shenker, Bruce J. (Frontiers in Cellular and Infection Microbiology, 2016)
The multifunctional role of lipids as structural components of membranes, signaling molecules, and metabolic substrates makes them an ideal partner for pathogens to hijack host cell processes for their own survival. The properties and composition of unique membrane micro-domains such as membrane rafts make these regions a natural target for pathogens as it affords them an opportunity to hijack cell signaling and intracellular trafficking pathways. Cytolethal distending toxins (Cdts), members of the AB2 family of toxins are comprised of three subunits, the active, CdtB unit, and the binding, CdtA-CdtC unit. Cdts are cyclomodulins leading to cell cycle arrest and apoptosis in a wide variety of cell types. Cdts from several species share a requirement for membrane rafts, and often cholesterol specifically for cell binding and CdtB mediated cytotoxicity. In this review we focus on how host–cell membrane bilayer organization contributes to the cell surface association, internalization, and action of bacteria derived cytolethal distending toxins (Cdts), with an emphasis on Aggregatibacter actinomycetemcomitans Cdt.